The Dynamics of HMI in Medan Post-Covid: Internal, Social, and New Politics - AL-Bukhori, Afif Aiman; Rohani , Laila (Journal La Sociale, 2025)
The COVID-19 pandemic has brought structural and functional changes in various aspects of life, including student organizations. This research examines the transformation of the Medan Branch of the Islamic Student Association (HMI) in responding to the challenges of the new normal era after the COVID-19 pandemic. The main focus of the study includes the internal dynamics of the organization, social influence on the campus environment and society, as well as the political role of HMI in the local context. This research uses a qualitative approach with a case study method. Data collection techniques involve in-depth interviews, participatory observation, and document analysis. The results show that HMI Medan Branch is able to adapt to the pandemic situation through digitalization of organizational activities, strengthening regeneration, and developing a political education model. Scientific discussion activities and leadership training are conducted online, while social relations are maintained through social media and other digital platforms. HMI also plays a significant role in educating students on post-pandemic social and political issues, while maintaining its ideological relevance in local dynamics. The findings provide a theoretical contribution in understanding student organizations as agents of social change in times of crisis. Practically, the results of this study can be a strategic reference for similar organizations in developing adaptation strategies, strengthening socio-political roles, and innovating regeneration in accordance with the needs of the times. Thus, this article offers a comprehensive picture of the resilience and transformation of student organizations in the face of major post-pandemic changes.